Disinformation and censorship on the web: Ethical implications for Information Science - Braga, Alexandre Eustáquio Perpétuo; Muriel-Torrado, Enrique (Advanced Notes in Information Science, 2023)
This essay addresses the frantic sharing of information and the ubiquity and availability of data the World Wide Web provides. It also examines the deleterious effects of disinformation, which goes viral through these same electronic infoways, and the efforts and alternatives conceived to contain this phenomenon. Disinformation influences the market, politics, and health, mobilizing people and sparking conflicts. In this scenario, the dawn of the instantaneous era is witnessed, whose outlines are defined by post-truth and characterized by the precedence of speed over reliability and source checking. The bibliographic research carried out for this text also exposes the risks inherent in the attempts to combat this phenomenon through censorship, thus reaffirming the importance of the commitment to ethics required of information scientists, with the findings pointing out that user education would be the most appropriate response to reducing the effects of disinformation in the context of this infodemic.